Sistem Informasi Dana Penunjang Pendidikan dan Kegiatan (DPPK) Berbasis Web di MA Nurul Jadid - Bambang Bambang; Helyatin Nisyak; Nadzirotul Fithriyah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
MA Nurul Jadid is one of the upper secondary education institutions under the auspices of Nurul Jadid Islamic Boarding School, Probolinggo Regency. The school offers three majors (Science, Social Studies, and Language) as well as three programs (excellent, regular, and religious) to accommodate students’ interests and needs. The management of the Educational and Activity Support Fund (DPPK) is still carried out manually using cash books and Microsoft Excel, which causes several issues such as recording errors, delayed reporting, and difficulties in real-time financial monitoring. This study aims to design and develop a web-based information system to improve administrative efficiency, data accuracy, and transparency in DPPK management. The research applies a mixed-methods approach, consisting of qualitative methods (interviews and observations) to identify user needs and challenges, and quantitative methods to measure system effectiveness through indicators such as recording accuracy and simplified reporting processes. The system was developed using the Laravel framework version 11 and MySQL database. The results show that the system is capable of automating the recording, monitoring, and reporting processes in a more structured and real-time manner. External testing of 10 respondents resulted in a 90% satisfaction rate. regarding ease of use and clarity of functions, indicating good user acceptance. In conclusion, the implementation of this system significantly improves DPPK financial management by reducing administrative errors and accelerating information access. Future developments may include integrating mobile platforms and technologies such as Node.js to enhance accessibility and flexibility.